Acute Urinary Retention Secondary to Urethral Lithiasis in a 4-Year-Old Boy: How We Managed This Rare Case - Planchamp, Thibault; Estournes, Pierre; Boileau, Adrien; Joseph, Solène; Piraprez, Mathilde; Laclergerie, Florian; Carfagna, Luana; Abbo, Olivier (European Journal of Pediatric Surgery Reports, 2025)
Urethral stone impaction (USI) is an extremely rare cause of acute urinary retention (AUR) in pediatric urology. Few case reports are available, and no consensus guidelines currently exist for managing this condition. We describe our management of such a case and provide a review of the relevant literature. A 4-year-old boy with no prior urological history presented to our emergency department with abdominal pain lasting 8 days. An ultrasound performed 5 days earlier identified a 7-mm stone at the ureterovesical junction. Symptomatic treatment with paracetamol and non-steroidal anti-inflammatory drugs was initiated. However, dysuria, painful penile swelling, and AUR developed 7 days after the onset of pain. A CT scan revealed bilateral hydronephrosis, urinary retention, and a 9-mm stone (980 Hounsfield Units) that had migrated to the proximal anterior urethra. Under general anesthesia, a suprapubic puncture removed 400 mL of urine for analysis. A 7.5-Fr cystoscope was used to identify an impacted stone at the base of the penile urethra. In situ lithotripsy was performed using a holmium laser to fragment the stone in the urethra. The fragments were then pushed into the bladder for complete disintegration. Intravesical fragments were subsequently removed with a Dormia basket. No urethral wounds were observed, and a 10-Fr catheter was placed. Recovery was uneventful, with catheter removal and spontaneous voiding on postoperative day 1. At the 3-month follow-up, the patient exhibited normal voiding and uroflowmetry. AUR secondary to USI is rare and lacks standardized management protocols in pediatric urology. Management of USI should be tailored to the size and location of the calculus, as well as the presence of any associated urethral pathology, with a preference for minimally invasive endoscopic surgery whenever possible. If necessary, urethral in situ laser lithotripsy appears to be a safe and effective treatment option to consider.
Keywords: urolithiasis; urethral calculi; pediatric urology; laser lithotripsy; endoscopy